Efek Penambahan Sari Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Kualitas Selai Lembaran Dami Nangka (Artocarpus heterophyllus) - Veronica Angga Puspita; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2019)
Straw from jackfruit so far is still considered a waste that is still thrown away by most people and even often becomes a problem that can pollute the environment. Jackfruit straw contains many of the same substances as fruit flesh such as protein, crude fiber, sugar and so on. Jackfruit straw has pectin which can be used as raw material in making jam. In making jam, fruits that have high acidity are also needed. Rosella contains vitamin C and flavonoids in the form of antosanin which can be used as flavor enhancers and natural dyes. The aim of this study was to determine the addition of rosella flower concentration that produced the best jackfruit straw jam based on the level of panelist preference (texture, color, taste), anthocyanin content, vitamin C content. This study used a completely randomized design with 5 treatments consisting of concentrations 0%, 10%, 20%, 30% and 40% with 5 repetitions. Analysis carried out by ANOVA test, if there is an effect of giving rosella juice then it will be followed by Duncan's test. The results showed that the addition of 40% roselle flower extract affected the level of preference for texture, color and taste. The addition of 40% has the highest total anthocyanin content of 45.22 mg / 100g and the total content of vitamin C in jackfruit straw sheet jam is 35.11 ppm. Keyword : Jam sheet, jackfruit, rosella essence, levels of pleasure, anthocyanin contains, vitamin C contains.